The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/hr.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pulse volume recording (PVR) parameters and ankle–brachial index (ABI) improves diagnostic accuracy for peripheral arterial disease compared with ABI alone

Abstract: The ankle-brachial index (ABI) measurement is widely used as a screening tool to detect peripheral arterial disease (PAD). With the advent of the oscillometric ABI device incorporating a system for the measurement of pulse volume recording (PVR), not only ABI but also other parameters, such as the percentage of mean arterial pressure (%MAP) and the upstroke time (UT), can be obtained automatically. The purpose of the present study was to compare the diagnostic accuracy for PAD with ABI alone with that of a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 13 publications
4
36
0
Order By: Relevance
“…%MAP indicates the presence of stenosis lesions in the region with 0.9 or lower ABI, but this ability may not be expected for regions with 0.91 or higher ABI. In the study reported by Hashimoto et al, 6) AUC of UT was 0.798, being almost consistent with that (0.810) in our study. These studies suggest that the diagnostic ability of UT is constantly high regardless of ABI being 0.9 or lower or 0.91 or higher.…”
Section: Diagnostic Accuracy Of Pvr Parameterssupporting
confidence: 81%
See 2 more Smart Citations
“…%MAP indicates the presence of stenosis lesions in the region with 0.9 or lower ABI, but this ability may not be expected for regions with 0.91 or higher ABI. In the study reported by Hashimoto et al, 6) AUC of UT was 0.798, being almost consistent with that (0.810) in our study. These studies suggest that the diagnostic ability of UT is constantly high regardless of ABI being 0.9 or lower or 0.91 or higher.…”
Section: Diagnostic Accuracy Of Pvr Parameterssupporting
confidence: 81%
“…Hashimoto et al 6) evaluated the diagnostic abilities of %MAP and UT using CTA as a reference in a group including many patients with 0.9 or lower ABI (range: 0.63-1.11), in which AUC of %MAP was 0.916. In contrast, in our study limiting patients to those with 0.91 or higher ABI, the diagnostic ability of %MAP decreased (AUC = 0.700).…”
Section: Diagnostic Accuracy Of Pvr Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The %MAP represents the percentage difference between the mean and maximum amplitude of the ankle pulse volume waveform [11]. An occluded artery with a atted waveform will result in an increased in %MAP value [10]. Therefore, the pulse volume recording at the ankle might be a sensitive indicator of an occlusive artery with a non-compressible pattern, which is frequently observed in patients with DM [21].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ABIs, vascular calcification and poor compressibility do not degrade PVRs. 12,16 As such, PVRs are considered a useful adjunct to segmental pressures in the vascular laboratory. 17,18 When combined with segmental pressures, PVRs have a reported diagnostic accuracy as high as 97%.…”
Section: Pulse Volume Recordingsmentioning
confidence: 99%